2000
DOI: 10.1144/jgs.157.1.151
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and origin of a polygonal fault system

Abstract: A fault array in South Australia, interpreted from a 3D onshore seismic survey, shows fault traces on the lowermost mapped horizon of a shale‐dominated sequence which outline polygonal cells averaging 1.4 km in diameter. The cell boundaries coincide approximately with the downward terminations and near convergence of conjugate pairs of normal faults. The pattern becomes less spatially ordered on higher horizons where faults still show a near‐isotropic strike distribution. Maximum throws, c. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(83 citation statements)
references
References 15 publications
4
79
0
Order By: Relevance
“…10 residual features are interpreted to be associated with tectonic subsidence related to plate motions and underlying mantle conditions, such as thermal relaxation (Gallagher and Lambeck, 1989;Gurnis et al, 1998;Watterson et al, 2000;Veevers, 2006;Heine et al, 2008). However, it has generally assumed that the flat-lying nature of most stratigraphic units in the Eromanga Basin underwent minimal tectonic deformation during or following deposition and that most of the units are relatively conformable.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…10 residual features are interpreted to be associated with tectonic subsidence related to plate motions and underlying mantle conditions, such as thermal relaxation (Gallagher and Lambeck, 1989;Gurnis et al, 1998;Watterson et al, 2000;Veevers, 2006;Heine et al, 2008). However, it has generally assumed that the flat-lying nature of most stratigraphic units in the Eromanga Basin underwent minimal tectonic deformation during or following deposition and that most of the units are relatively conformable.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…In typical blind normal faults and polygonal faults, the displacement patterns are commonly symmetric with depth. Notable exceptions are when a weak layer is present near the base or where a shallow propagating fault approaches the free surface (sediment-water interface); in these cases, a significant increase in local displacement gradients is generally observed [e.g., Watterson et al, 2000;Nicol et al, 2003;Stuevold et al, 2003].…”
Section: Field Observationsmentioning
confidence: 99%
“…For comparison, we plot the maximum throw d versus fault height H in Figure 2 for a collection of 629 faults in polygonal systems worldwide (Note: height H is measured in the vertical direction). These data were selected from polygonal fault arrays where the vertical displacement variation was generally symmetric about a mid-point (see Figure 1b), and where there was little evidence of anomalously weak layers near the base because they distort displacement distribution on individual faults [Watterson et al, 2000]. Similarly, the aspect ratio of faults is known to impact scaling relationships for faults [Nicol et al, 1996], hence, these data come from faults with aspect ratios strike lengthto-height between 0.8 and 2.6.…”
Section: Field Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was demonstrated that low coefficients of residual friction in fine-grained sediments might be key to the formation of the polygonal system, and there was no evidence that nucleation of those faults that evolve into polygonal systems differs fundamentally from the processes involved in the nucleation of conventional faults in soft sediments [8]. Previous studies show that polygonal faults often initiate at shallow burial depth [2,7,29]. With increasing buried depth, compacted dewatering continuously occurs in layers underlying polygonal faults, and expelled fluids migrate up through polygonal faults and rock porosities to arrive at the seabed.…”
Section: Focused Fluid Flow Associated With Polygonal Faultmentioning
confidence: 99%